Preparation method of molybdenum-copper alloy profile

By preparing copper-coated molybdenum composite powder and performing cold pressing molding, permeability sintering, laminate rolling and grinding processing, the problems of low density and poor thermal conductivity in the preparation of traditional molybdenum copper alloys are solved, and efficient preparation of molybdenum copper alloy profiles is achieved, with excellent performance and economical processes.

CN115740458BActive Publication Date: 2025-03-18XIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211618615.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-15
Publication Date
2025-03-18
Estimated Expiration
2042-12-15

AI Technical Summary

Technical Problem

The problems of low density, poor thermal conductivity and high expansion coefficient during the preparation of traditional molybdenum copper alloys.

Method used

By preparing copper-coated molybdenum composite powder, cold press molding and permeability sintering, and then laminated rolling and grinding, a molybdenum copper alloy profile with uniform structure distribution and excellent properties was obtained.

Benefits of technology

The problems of low density, poor thermal conductivity and high linear expansion coefficient of molybdenum copper alloy sheets are solved, the mechanical and physical properties of the material are improved, and the process is economical and fast.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115740458B_ABST
    Figure CN115740458B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a molybdenum-copper alloy profile, which specifically comprises the following steps: step 1, preparing copper-coated molybdenum composite powder; step 2, preparing mixed powder according to the product obtained in step 1, supplementing molybdenum powder and inducing copper powder; step 3, cold pressing the mixed powder prepared in step 2, step 4, performing infiltration sintering on the cold pressing forming in step 3 to obtain a molybdenum-copper alloy billet; step 5, laminating and rolling the molybdenum-copper alloy billet after infiltration sintering in step 4 to obtain a molybdenum-copper alloy plate; step 6, grinding the molybdenum-copper alloy plate obtained in step 5. The copper-molybdenum alloy profile prepared by the present invention solves the problems of low density, poor thermal and electrical conductivity, and high expansion coefficient existing in the preparation process of traditional molybdenum-copper alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material preparation and modification processing, and relates to a method for preparing a molybdenum-copper alloy profile. Background Art

[0002] With the development of integrated circuits in the field of microelectronics technology towards large storage capacity and high speed, and the development of assembly parts towards miniaturization and thinness, the packaging heat sink material is required to meet the "three highs and one low" requirements, namely, ① the thermal conductivity and electrical conductivity of the material should be good, and the heat generated by the semiconductor chip during operation should be dissipated in time; ② the material should have a low thermal expansion coefficient, good matching, brazing and corrosion resistance; ③ the material should have sufficient strength, rigidity and formability; ④ the cost of the material should be as low as possible to meet the requirements of large-scale commercial applications. So far, traditional single metals (Al, Cu, Mo, W) or alloys (Kovar alloy, Invar alloy) can no longer meet the requirements of high-integration chips and circuits. Metal-based molybdenum-copper composite materials are a uniformly mixed organization of two-phase monomers composed of molybdenum and copper, which are neither mutually soluble nor form intermetallic compounds. Molybdenum-copper alloys have the excellent properties of high melting point, high density, strong electrocorrosion resistance, low thermal expansion coefficient of Mo and high electrical conductivity, thermal conductivity, certain plasticity of Cu, and the corresponding mechanical and physical properties of the material can be controlled and adjusted by changing its composition ratio. It is this characteristic that makes molybdenum-copper alloys widely used in electronic packaging, heat sinks and other fields. However, due to the large difference in melting points between molybdenum and copper, extremely low solubility under equilibrium conditions, and significant difference in electronegativity, the alloy materials prepared by traditional processes have low density and poor electrical and thermal conductivity. Therefore, it is very necessary to find an economical and efficient technical process to prepare molybdenum-copper alloy materials with better performance. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a molybdenum-copper alloy profile. The copper-molybdenum alloy profile prepared by the method solves the problems of low density, poor thermal and electrical conductivity, and high expansion coefficient existing in the traditional molybdenum-copper alloy preparation process.

[0004] The technical solution adopted by the present invention is a method for preparing a molybdenum-copper alloy profile, which specifically comprises the following steps:

[0005] Step 1, preparing copper-coated molybdenum composite powder;

[0006] Step 2, preparing a mixed powder according to the product obtained in step 1, supplementing molybdenum powder and induced copper powder;

[0007] Step 3, cold pressing the mixed powder prepared in step 2;

[0008] Step 4, performing infiltration sintering on the cold pressing forming in step 3 to obtain a molybdenum-copper alloy billet;

[0009] Step 5, performing laminate rolling on the molybdenum-copper alloy ingot after solution infiltration and sintering in step 4 to obtain a molybdenum-copper alloy plate;

[0010] Step 6, grinding the molybdenum-copper alloy plate obtained in step 5.

[0011] The present invention is also characterized in that:

[0012] The specific process of step 1 is:

[0013] Step 1.1, ultrasonically cleaning the molybdenum powder in anhydrous ethanol solvent for 15 to 30 minutes, and drying and baking; Step 1.2, cleaning the sample prepared in step 1.1 in a sodium hydroxide solution with a concentration of 10 to 20 g / L for 25 to 40 minutes to remove grease attached to the surface, and immersing the degreased molybdenum powder in hydrochloric acid with a concentration of 35% to 40%, and roughening it for 25 to 40 minutes;

[0014] Step 1.3, adding the molybdenum powder treated in step 1.2 to the chemical plating solution, the chemical plating process is carried out in a heat collecting magnetic stirrer, the heat collecting magnetic stirrer maintains the plating solution temperature at 55-60°C, 10%-15% sodium hydroxide solution is added dropwise to the chemical plating solution, and the pH value of the plating solution is adjusted to 12-13. When the specified pH value range is reached, after a gestation period of 25-30s, the reaction begins, and bubbles gradually escape. When the bubbles in the plating solution disappear, the chemical plating is completed;

[0015] Step 1.4, curing and sintering at 300-500° C. for 1-2 hours in a reducing atmosphere to obtain a copper-coated molybdenum composite powder, wherein the copper content in the coated powder accounts for 17%-19%.

[0016] The specific process of step 2 is: mechanically mix the copper-coated molybdenum composite powder prepared in step 1 with the supplementary molybdenum powder and the induced copper powder in a mixer for 30 to 90 minutes, add 10 to 20 mL / kg of gasoline solvent during mixing, and finally obtain a uniform mixed powder.

[0017] The specific process of step 3 is: weigh the mixed powder obtained in step 2, load it into the cavity of a steel pressing mold for cold pressing, select a pressing pressure of 600 to 800 MPa, hold the pressure for 10 to 15 seconds, and finally demold to obtain a block of determined size and shape.

[0018] The specific process of step 4 is: the green body formed by cold pressing in step 3 is placed in a graphite boat or a ceramic boat, the copper block to be infiltrated is filled with alumina sand, and then the temperature is raised to 1300-1350°C at a rate of 6-10°C / min under a protective atmosphere, the gas flow rate is 1-2L / h, and after staying for 90-120 minutes, it is cooled with the furnace to obtain a sintered molybdenum-copper alloy.

[0019] The specific process of step 5 is as follows: a layer of cold-rolled steel plate with a thickness of about 5 to 10 mm is added to the upper and lower parts of the molybdenum-copper alloy block obtained by solution infiltration and sintering in step 4, an anti-sticking nano-Al2O3 coating is applied between the rolled plate layers, the rolling temperature is 700 to 800°C, and then different passes are rolled on the rolling mill, and finally the temperature is 300 to 330°C, the temperature is kept for 1 to 2 hours, and the molybdenum-copper alloy plate is obtained after annealing and heat treatment and then processed by machine tools.

[0020] The specific process of step 6 is: the molybdenum-copper alloy plate obtained in step 5 is firstly sandblasted to remove the oxide on the surface, and then the upper and lower surfaces are ground on a surface grinder to a surface roughness of not less than Ra0.3, and finally cut into the required size.

[0021] The beneficial effects of the present invention are that the preparation method of the molybdenum-copper alloy profile provided by the present invention not only has a large range of variation in the thickness of the obtained plate (which can be arbitrarily required between 0.1 and 5 mm), but also effectively solves the difficult problems of poor uniformity of tissue distribution, low density, poor thermal and electrical conductivity, and high linear expansion coefficient in the preparation of molybdenum-copper alloy plates. The prepared molybdenum-copper composite material has good comprehensive properties such as mechanical properties and physical properties, and has the characteristics of no chips, less chips, economy and speed. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of a thin plate rolling assembly used in the method for preparing a molybdenum-copper alloy profile of the present invention;

[0023] Figure 2 (a) to (c) are SEM and EDS photos of the copper-coated molybdenum composite powder prepared by chemical plating technology in Example 1 of the method for preparing the molybdenum-copper alloy profile of the present invention;

[0024] Figure 3 (a) and (b) are metallographic microstructure photographs of Mo70Cu obtained by Example 1 of the method for preparing molybdenum-copper alloy profiles of the present invention before and after rolling.

[0025] In the figure, 1. rolling roller, 2. cold-rolled steel plate, 3. Al2O3 coating, 4. alloy billet. DETAILED DESCRIPTION

[0026] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0027] The preparation method of the molybdenum-copper alloy profile of the present invention specifically comprises the following steps:

[0028] Step 1, chemical copper plating on molybdenum powder;

[0029] The commercially available original molybdenum powder (particle size of 5-10 microns) was ultrasonically cleaned in anhydrous ethanol solvent for 15-30 minutes and dried. Subsequently, the sample was cleaned in a 10-20g / L sodium hydroxide solution for 25-40 minutes to remove grease and other residues attached to the surface. The degreased molybdenum powder was soaked in a 35%-40% hydrochloric acid solution and roughened for 25-40 minutes to improve the surface morphology of the molybdenum powder and make copper better adhere to the surface of the molybdenum powder. Finally, the pretreated molybdenum powder is added to the chemical plating solution. The chemical plating process is carried out in a heat-collecting magnetic stirrer. The heat-collecting magnetic stirrer maintains the plating solution temperature at 55-60°C and the rotor speed at 300r / min. 10%-15% sodium hydroxide solution is added dropwise to the plating solution to adjust the pH value of the plating solution to 12-13. When the specified pH value range is reached, after a gestation period of 25-30s, the reaction begins, and bubbles gradually escape. When the plating solution changes from the initial blue-gray color to dark red, the bubbles in the plating solution disappear, and the chemical plating is completed. After each stage of the reaction is completed, it is necessary to wash it with deionized water 3-5 times and then with alcohol 2-4 times. The composition of the chemical plating solution is shown in Table 1. Finally, it is cured and sintered at 300-500°C for 1-2 hours in a reducing atmosphere (hydrogen or vacuum) to obtain a copper-coated molybdenum composite powder with adjustable composition, particle size, and sphericity. The copper content in the coated powder accounts for 17%-19%.

[0030] Table 1 Chemical plating solution parameters and ratios

[0031] Element concentration content(%) Copper sulfate pentahydrate 20g / L 27.8 Formaldehyde solution 20ml / L 14.8 Potassium Sodium Tartrate 10g / L 19.1 Disodium EDTA 18g / L 38.3

[0032] Step 2, mixing;

[0033] The copper-coated molybdenum composite powder prepared in step 1 (the copper content in the coated powder is calculated as 18%), the coated powder value is taken in priority principle, the coated powder is matched with the supplementary molybdenum powder and the induced copper powder (particle size is 50-80 microns), and the proportion of the three powders is calculated according to the required percentage as shown in Table 2, and the calculated copper powder, molybdenum powder and copper-coated molybdenum powder are mechanically mixed in a mixer for 30-90 minutes. During the mixing, 10-20mL / kg of solvent gasoline is added to speed up the mixing efficiency, and 2% of sodium butadiene rubber solution is added at the same time (the sodium butadiene rubber is dissolved in solvent gasoline to reach a saturated solution), and finally a uniform mixed powder is obtained.

[0034] Table 2 Proportion of molybdenum-copper alloy powders with different compositions (%)

[0035]

[0036] Step 3, molding;

[0037] First, the molybdenum-copper alloy billet is formed into a rectangular block with a size of 100 mm × 60 mm × 10 mm, and the mass of molybdenum-copper alloy plates with different compositions is calculated (the method is that the mass of the molybdenum-copper alloy billet = the volume of the billet 60 cm 3 ×The theoretical density of this component is shown in Table 2×85%), then weigh the corresponding mixed powder in step 2, load it into the cavity of a high-speed steel press mold for cold pressing, select a pressing pressure of 600-800MPa, hold the pressure for 10-15s, and finally demold to obtain a block of determined size and shape.

[0038] Step 4, solution infiltration sintering;

[0039] Place the green compact formed by cold pressing in step 3 in a graphite boat or a ceramic boat, and place the copper block to be infiltrated (which can be made of pure copper profiles or formed of pure copper powder) on the upper end of the compact (the specific amount is calculated by the mass of infiltrated copper = the volume of the compact 60cm 3 ×Theoretical density of this component is shown in Table 2×15%), and the surrounding is filled with alumina sand with a particle size of 100 mesh. Then it is slowly heated in a high-temperature atmosphere protection furnace (heating rate is 6-10℃ / min) to 1300-1350℃. The protective atmosphere used is hydrogen, which can not only reduce the oxygen adsorbed by the powder or the briquette, but also facilitate the diffusion of atoms in the briquette and accelerate the densification of the briquette. The gas flow rate is 1-2L / h. After staying for 90-120min, it is cooled with the furnace, and then a sintered molybdenum-copper alloy is obtained.

[0040] Step 5, lamination rolling;

[0041] A layer of cold-rolled steel plate with a thickness of about 5 to 10 mm (the plane size of the steel plate is 1 to 3 times larger than that of the billet) is added to the upper and lower parts of the molybdenum-copper alloy billet obtained by the solution infiltration sintering in step 4, and an anti-sticking nano-Al2O3 coating is applied between the rolled plate layers. Figure 1 As shown, the stacked rolling assembly includes a roller 1, a cold-rolled steel plate 2, an Al2O3 coating 3 and an alloy billet 4; the rolling temperature is 700-800°C, and then different passes are carried out on the rolling mill (after each pass, it must be placed in a heating furnace and heated to the above temperature), and finally the molybdenum-copper alloy block is rolled into a plate with the required size, thickness and high surface flatness. Finally, it is kept at 300-330°C for 1-2 hours, annealed and heat treated, and then processed by a machine tool to obtain a thin composite plate with size, structure and performance that meet the requirements. This stacked rolling not only prevents the surface from being oxidized, but also can obtain a thin plate with uniform thickness and smooth surface (the thickness can reach about 0.1 mm). At the same time, in order to improve the rolling efficiency, multi-layer rolling can be performed (multiple alloy billets are stacked at the same time, but each alloy billet layer must be separated by a steel plate).

[0042] Step 6, grinding;

[0043] The molybdenum-copper alloy plate that meets the size requirements obtained in step 5 is firstly subjected to solid sandblasting to remove the surface oxide, and then the upper and lower surfaces are ground on a surface grinder with a surface roughness of not less than Ra0.3, and finally cut into the required size to achieve the molybdenum-copper alloy plate required by the user.

[0044] Example 1

[0045] Mo70Cu30 alloy plates with a size of 100×100×1 mm were prepared.

[0046] Step 1, chemical copper plating on molybdenum powder;

[0047] The commercially available original molybdenum powder (particle size of 5 to 10 microns) was ultrasonically cleaned in anhydrous ethanol solvent for 15 minutes and dried. Subsequently, the sample was cleaned in a 10g / L sodium hydroxide solution for 25 minutes to remove grease and other residues attached to the surface. The degreased molybdenum powder was soaked in a 35% hydrochloric acid concentration and roughened for 25 minutes to improve the surface morphology of the molybdenum powder and make copper better attached to the surface of the molybdenum powder. Finally, the pretreated molybdenum powder was added to the chemical plating solution. The chemical plating process was carried out in a heat-collecting magnetic stirrer. The heat-collecting magnetic stirrer maintained the plating solution temperature at 60°C and the rotor speed at 300r / min. 15% sodium hydroxide solution was added dropwise to the plating solution, and the pH value of the plating solution was adjusted to 13. When the specified pH value range was reached, the reaction began after a 25s incubation period. Bubbles will gradually escape during the reaction, and when the plating solution changes from the initial blue-gray color to dark red, the chemical plating is completed. After each stage of the reaction is completed, it is necessary to wash it with deionized water for 3 times and then with alcohol for 2 times. Finally, it is cured and sintered at 300°C for 1 hour in a reducing atmosphere (hydrogen or vacuum) to obtain a coated powder with adjustable composition, particle size and sphericity and a coating ratio of 18%.

[0048] Step 2, mixing;

[0049] Directly weigh 586.26 g of coated powder according to the ratio.

[0050] Step 3, molding;

[0051] The powder weighed in step 2 is placed in a high-speed steel press mold for cold pressing. The selected pressing pressure is 450 MPa, the holding time is 10 s, and the Mo70Cu30 compact is obtained after demolding.

[0052] Step 4, solution infiltration sintering;

[0053] The cold-pressed green sheet formed in step 3 is placed in a graphite boat, and the copper block to be infiltrated (pure copper profile is used directly) is placed on the upper end of the green sheet, and the surrounding area is filled with alumina sand with a particle size of 100 mesh. Then it is slowly heated in a high-temperature atmosphere protection furnace (heating rate is 8°C / min) to 1300°C, and the protective atmosphere used is hydrogen, and the gas flow rate is 1.1L / h. After staying for 90 minutes, it is cooled with the furnace, and then a sintered molybdenum-copper alloy green sheet is obtained.

[0054] Step 5, lamination rolling;

[0055] Add a layer of cold-rolled steel plate with a thickness of about 5 to 10 mm (the plane size of the steel plate is 1 to 3 times larger than the billet) on the top and bottom of the molybdenum-copper alloy billet obtained by infiltration sintering in step 4, apply an anti-sticking nano-Al2O3 coating between the plate layers, heat the assembly to 800°C, and then perform different passes on the rolling mill (after each pass, it must be placed in a heating furnace and heated to the above temperature), and finally the molybdenum-copper alloy block is rolled into a plate with the required thickness and high surface flatness. After 300°C, keep warm for 1.5 hours, anneal and heat treat, and then lathe process to obtain a thin composite plate with a structure shape and performance that meets the requirements.

[0056] Step 6, grinding;

[0057] The molybdenum-copper alloy plate that meets the size requirements obtained in step 5 is firstly subjected to solid sandblasting to remove the oxide on the surface, and then the upper and lower surfaces are ground on a surface grinder, and the surface roughness is not less than Ra0.3, so as to finally achieve the molybdenum-copper alloy plate required by the user.

[0058] During the preparation process of this Example 1, Figure 2 (a) is the SEM morphology of copper-coated molybdenum composite powder. It can be seen that small and uniform spherical or dumbbell-shaped particles grow on the surface of Mo powder. The surface of Mo powder is completely coated, and the coating effect is good. The shape of the coated powder tends to be spherical. The particle size of the coated powder is about 4-6μm. This is to verify the core-shell structure of the composite powder. Figure 2 (b)(c) are the cross-sectional structure and line scanning distribution diagram of the core-shell structure copper-coated molybdenum composite powder. It can be seen that the outer layer element of a single powder particle is Cu, and the inner layer element is Mo. The coating is clearly visible, and the coating thickness is 1 μm.

[0059] Figure 3 (a) is a photo of the structure of Mo70Cu30 alloy before rolling, in which the granular part is copper and the matrix is ​​molybdenum. It can be seen from the figure that the granular copper phase is evenly distributed in the matrix molybdenum phase, and the copper phase accounts for about 30% of the total volume. The two-phase structure is evenly distributed, without obvious defects such as pores and agglomerations, and no other phases are seen in the structure. Figure 3(b) is a microstructure photo of the Mo70Cu30 alloy along the longitudinal section of the rolling direction. It can be seen from the figure that the molybdenum particles have undergone obvious plastic deformation after hot rolling, that is, they have been elongated to a certain extent along the rolling direction. It can also be seen that the alloy has obvious rolling streamlines after rolling, the network structure of copper is more obvious, and the copper phase distribution is more dispersed and uniform. The dense and uniform network distribution of the copper phase greatly improves the density of the molybdenum-copper alloy, which can effectively improve the electrical and thermal conductivity of the material.

[0060] Example 2

[0061] A Mo60Cu40 alloy plate material with a size of 200×200×1 mm was prepared.

[0062] Step 1: Chemical copper plating on molybdenum powder

[0063] The commercially available original molybdenum powder (particle size of 5 to 10 microns) was ultrasonically cleaned in anhydrous ethanol solvent for 20 minutes and dried. Subsequently, the sample was cleaned in a 10g / L sodium hydroxide solution for 25 minutes to remove grease and other residues attached to the surface. The degreased molybdenum powder was soaked in a 35% hydrochloric acid concentration and roughened for 25 minutes to improve the surface morphology of the molybdenum powder and make copper better attached to the surface of the molybdenum powder. Finally, the pretreated molybdenum powder was added to the chemical plating solution. The chemical plating process was carried out in a heat-collecting magnetic stirrer. The heat-collecting magnetic stirrer maintained the plating solution temperature at 60°C and the rotor speed at 300r / min. 15% sodium hydroxide solution was added dropwise to the plating solution, and the pH value of the plating solution was adjusted to 13. When the specified pH value range was reached, the reaction began after a 25s incubation period. Bubbles will gradually escape during the reaction, and when the plating solution changes from the initial blue-gray color to dark red, the chemical plating is completed. After each stage of the reaction is completed, it is necessary to wash it with deionized water for 3 times and then with alcohol for 2 times. Finally, it is cured and sintered at 300°C for 1 hour in a reducing atmosphere (hydrogen or vacuum) to obtain a coated powder with adjustable composition, particle size and sphericity and a coating ratio of 18%.

[0064] Step 2, mixing;

[0065] According to the proportion, 703.54g of coated powder and 115.66g of induced copper powder were weighed. The weighed induced copper powder and coated powder were mechanically mixed in a mixer for 50 minutes. During the mixing, 18mL / kg of solvent gasoline was added to speed up the mixing efficiency, and finally a uniform mixed powder was obtained.

[0066] Step 3, molding;

[0067] The powder weighed in step 2 is placed in a high-speed steel press mold for cold pressing. The selected pressing pressure is 520 MPa, the holding time is 12 s, and the Mo60Cu40 compact is obtained after demolding.

[0068] Step 4: Infiltration and sintering

[0069] The cold-pressed green sheet formed in step 3 is placed in a graphite boat, and the copper block to be infiltrated (pure copper profile is used directly) is placed on the upper end of the green sheet, and the surrounding area is filled with alumina sand with a particle size of 100 mesh. Then it is slowly heated in a high-temperature atmosphere protection furnace (heating rate is 8°C / min) to 1300°C, and the protective atmosphere used is hydrogen, and the gas flow rate is 1.1L / h. After staying for 90 minutes, it is cooled with the furnace, and then a sintered molybdenum-copper alloy green sheet is obtained.

[0070] Step 5, lamination rolling;

[0071] Add a layer of cold-rolled steel plate with a thickness of about 5 to 10 mm (the plane size of the steel plate is 1 to 3 times larger than the billet) on the top and bottom of the molybdenum-copper alloy billet obtained by solution infiltration sintering in step 4, apply an anti-sticking nano-Al2O3 coating between the plate layers, heat the assembly to 800°C, and then perform different passes of rolling on the rolling mill (after each pass, it must be placed in a heating furnace and heated to the above temperature), and finally the molybdenum-copper alloy block is rolled into a plate with the required thickness and high surface flatness. After 300°C, keep warm for 1.5 hours, anneal and heat treat, and then lathe process to obtain a thin composite plate with size structure and performance that meets the requirements.

[0072] Step 6, grinding;

[0073] The molybdenum-copper alloy plate that meets the size requirements obtained in step 5 is firstly subjected to solid sandblasting to remove the oxide on the surface, and then the upper and lower surfaces are ground on a surface grinder, and the surface roughness is not less than Ra0.3, so as to finally achieve the molybdenum-copper alloy plate required by the user.

[0074] Example 3

[0075] Mo50Cu50 alloy sheet material with a size of 150×150×0.5 mm was prepared.

[0076] Step 1: Chemical copper plating on molybdenum powder

[0077] The commercially available original molybdenum powder (particle size of 5 to 10 microns) was ultrasonically cleaned in anhydrous ethanol solvent for 25 minutes and dried. Subsequently, the sample was cleaned in a 10g / L sodium hydroxide solution for 25 minutes to remove grease and other residues attached to the surface. The degreased molybdenum powder was soaked in a 35% hydrochloric acid concentration and roughened for 25 minutes to improve the surface morphology of the molybdenum powder and make copper better attached to the surface of the molybdenum powder. Finally, the pretreated molybdenum powder was added to the chemical plating solution. The chemical plating process was carried out in a heat-collecting magnetic stirrer. The heat-collecting magnetic stirrer maintained the plating solution temperature at 60°C and the rotor speed at 300r / min. 15% sodium hydroxide solution was added dropwise to the plating solution, and the pH value of the plating solution was adjusted to 13. When the specified pH value range was reached, the reaction began after a 25s incubation period. Bubbles will gradually escape during the reaction, and when the plating solution changes from the initial blue-gray color to dark red, the chemical plating is completed. After each stage of the reaction is completed, it is necessary to wash it with deionized water for 3 times and then with alcohol for 2 times. Finally, it is cured and sintered at 300°C for 1 hour in a reducing atmosphere (hydrogen or vacuum) to obtain a coated powder with adjustable composition, particle size and sphericity and a coating ratio of 18%.

[0078] Step 2, mixing;

[0079] Weigh 353.62g of coated powder and 131.18g of induced copper powder according to the proportion. Mechanically mix the weighed induced copper powder and coated powder in a mixer for 35 minutes. Add 18mL / kg of solvent gasoline during mixing to speed up the mixing efficiency, and finally obtain a uniform mixed powder.

[0080] Step 3, molding;

[0081] The powder weighed in step 2 is placed in a high-speed steel press mold for cold pressing. The selected pressing pressure is 500 MPa, the holding time is 10 s, and the Mo50Cu50 compact is obtained after demolding.

[0082] Step 4, solution infiltration sintering;

[0083] The cold-pressed green sheet formed in step 3 is placed in a graphite boat, and the copper block to be infiltrated (pure copper profile is used directly) is placed on the upper end of the green sheet, and the surrounding area is filled with alumina sand with a particle size of 100 mesh. Then it is slowly heated in a high-temperature atmosphere protection furnace (heating rate is 8°C / min) to 1300°C, and the protective atmosphere used is hydrogen, and the gas flow rate is 1.1L / h. After staying for 90 minutes, it is cooled with the furnace, and then a sintered molybdenum-copper alloy green sheet is obtained.

[0084] Step 5, lamination rolling;

[0085] Add a layer of cold-rolled steel plate with a thickness of about 5 to 10 mm (the plane size of the steel plate is 1 to 3 times larger than the billet) on the top and bottom of the molybdenum-copper alloy billet obtained by solution infiltration sintering in step 4, apply an anti-sticking nano-Al2O3 coating between the plate layers, heat the assembly to 800°C, and then perform different passes of rolling on the rolling mill (after each pass, it must be placed in a heating furnace and heated to the above temperature), and finally the molybdenum-copper alloy block is rolled into a plate with the required thickness and high surface flatness. After 300°C, keep warm for 1.5 hours, anneal and heat treat, and then lathe process to obtain a thin composite plate with size structure and performance that meets the requirements.

[0086] Step 6, grinding;

[0087] The molybdenum-copper alloy plate that meets the size requirements obtained in step 5 is firstly subjected to solid sandblasting to remove the oxide on the surface, and then the upper and lower surfaces are ground on a surface grinder, and the surface roughness is not less than Ra0.3, so as to finally achieve the molybdenum-copper alloy plate required by the user.

[0088] Example 4

[0089] Mo80Cu20 alloy sheet material with a size of Φ100mm×1mm was prepared.

[0090] Step 1, chemical copper plating on molybdenum powder;

[0091] The commercially available original molybdenum powder (particle size of 5 to 10 microns) was ultrasonically cleaned in anhydrous ethanol solvent for 30 minutes and dried. Subsequently, the sample was cleaned in a 10g / L sodium hydroxide solution for 25 minutes to remove grease and other residues attached to the surface. The degreased molybdenum powder was soaked in a 35% hydrochloric acid concentration and roughened for 25 minutes to improve the surface morphology of the molybdenum powder and make copper better attached to the surface of the molybdenum powder. Finally, the pretreated molybdenum powder was added to the chemical plating solution. The chemical plating process was carried out in a heat-collecting magnetic stirrer. The heat-collecting magnetic stirrer maintained the plating solution temperature at 60°C and the rotor speed at 300r / min. 15% sodium hydroxide solution was added dropwise to the plating solution, and the pH value of the plating solution was adjusted to 13. When the specified pH value range was reached, the reaction began after a 25s incubation period. Bubbles will gradually escape during the reaction, and when the plating solution changes from the initial blue-gray color to dark red, the chemical plating is completed. After each stage of the reaction is completed, it is necessary to wash it with deionized water for 3 times and then with alcohol for 2 times. Finally, it is cured and sintered at 300°C for 1 hour in a reducing atmosphere (hydrogen or vacuum) to obtain a coated powder with adjustable composition, particle size and sphericity and a coating ratio of 18%.

[0092] Step 2, mixing;

[0093] Directly weigh 582.76 g of coated powder according to the ratio.

[0094] Step 3, molding;

[0095] The powder weighed in step 2 is placed in a high-speed steel press mold for cold pressing. The selected pressing pressure is 500 MPa, the holding time is 10 s, and after demolding, a Mo50Cu50 compact is obtained.

[0096] Step 4, solution infiltration sintering;

[0097] The cold-pressed green sheet formed in step 3 is placed in a graphite boat, and the copper block to be infiltrated (pure copper profile is used directly) is placed on the upper end of the green sheet, and the surrounding area is filled with alumina sand with a particle size of 100 mesh. Then it is slowly heated in a high-temperature atmosphere protection furnace (heating rate is 8°C / min) to 1300°C, and the protective atmosphere used is hydrogen, and the gas flow rate is 1.1L / h. After staying for 90 minutes, it is cooled with the furnace, and then a sintered molybdenum-copper alloy green sheet is obtained.

[0098] Step 5, lamination rolling;

[0099] Add a layer of cold-rolled steel plate with a thickness of about 5 to 10 mm (the plane size of the steel plate is 1 to 3 times larger than the billet) on the top and bottom of the molybdenum-copper alloy billet obtained by solution infiltration sintering in step 4, apply an anti-sticking nano-Al2O3 coating between the plate layers, heat the assembly to 800°C, and then perform different passes of rolling on the rolling mill (after each pass, it must be placed in a heating furnace and heated to the above temperature), and finally the molybdenum-copper alloy block is rolled into a plate with the required thickness and high surface flatness. After 300°C, keep warm for 1.5 hours, anneal and heat treat, and then lathe process to obtain a thin composite plate with size structure and performance that meets the requirements.

[0100] Step 6, grinding;

[0101] The molybdenum-copper alloy plate that meets the size requirements obtained in step 5 is firstly subjected to solid sandblasting to remove the oxide on the surface, and then the upper and lower surfaces are ground on a surface grinder, and the surface roughness is not less than Ra0.3, so as to finally achieve the molybdenum-copper alloy plate required by the user.

[0102] Table 3 Properties of the prepared molybdenum-copper alloy plates or sheets

[0103]

Claims

1. A method for preparing a molybdenum-copper alloy profile, characterized in that: The specific steps include: Step 1, preparing copper-coated molybdenum composite powder; The specific process of step 1 is as follows: Step 1.1, ultrasonically cleaning the molybdenum powder in anhydrous ethanol solvent for 15 to 30 minutes, and drying and baking; Step 1.2, cleaning the sample prepared in step 1.1 in a 10 to 20 g / L sodium hydroxide solution for 25 to 40 minutes to remove grease attached to the surface, and immersing the degreased molybdenum powder in a 35% to 40% hydrochloric acid solution for coarsening for 25 to 40 minutes; Step 1.3, adding the molybdenum powder treated in step 1.2 to the chemical plating solution, the chemical plating process is carried out in a heat collecting magnetic stirrer, the heat collecting magnetic stirrer maintains the plating solution temperature at 55-60°C, 10%-15% sodium hydroxide solution is added dropwise to the chemical plating solution, and the pH value of the plating solution is adjusted to 12-13. When the specified pH value range is reached, after a gestation period of 25-30s, the reaction begins, and bubbles gradually escape. When the bubbles in the plating solution disappear, the chemical plating is completed; Step 1.4, curing and sintering at 300-500° C. for 1-2 hours in a reducing atmosphere to obtain a copper-coated molybdenum composite powder, wherein the copper content in the coated powder accounts for 17%-19%; Step 2, preparing a mixed powder according to the product obtained in step 1, supplementing molybdenum powder and induced copper powder; The specific process of step 2 is: mechanically mixing the copper-coated molybdenum composite powder prepared in step 1 with the supplementary molybdenum powder and the induced copper powder in a mixer for 30 to 90 minutes, adding 10 to 20 mL / kg of solvent gasoline during mixing, and finally obtaining a uniform mixed powder; Step 3, cold pressing the mixed powder prepared in step 2; Step 4, performing infiltration sintering on the cold pressing forming in step 3 to obtain a molybdenum-copper alloy billet; The specific process of step 4 is: placing the green body formed by cold pressing in step 3 in a graphite boat or a ceramic boat, filling the copper block to be infiltrated with alumina sand, and then heating the green body at 6 to 10 °C in a protective atmosphere. o C / min and heat up to 1300~1350 o C, the gas flow rate is 1~2L / h, and after staying for 90~120 minutes, it is cooled with the furnace, and then a sintered molybdenum-copper alloy is obtained; Step 5, performing laminate rolling on the molybdenum-copper alloy ingot after solution infiltration and sintering in step 4 to obtain a molybdenum-copper alloy plate; The specific process of step 5 is as follows: a layer of cold-rolled steel plate with a thickness of 5 to 10 mm is added to the upper and lower parts of the molybdenum-copper alloy block obtained by solution infiltration and sintering in step 4, an anti-sticking nano-Al2O3 coating is applied between the rolled plate layers, the rolling temperature is 700 to 800°C, and then different passes are rolled on a rolling mill, and finally the molybdenum-copper alloy plate is obtained by annealing and heat treatment and then machined; Step 6, grinding the molybdenum-copper alloy plate obtained in step 5.

2. The method for preparing the molybdenum-copper alloy profile according to claim 1, characterized in that: The specific process of step 3 is: weigh the mixed powder obtained in step 2, load it into the cavity of a steel pressing mold for cold pressing, select a pressing pressure of 600-800 MPa, hold the pressure for 10-15 seconds, and finally demold to obtain a block of determined size and shape.

3. The method for preparing the molybdenum-copper alloy profile according to claim 1, characterized in that: The specific process of step 6 is: firstly, the molybdenum-copper alloy plate obtained in step 5 is subjected to solid sandblasting to remove the oxide on the surface, then the upper and lower surfaces are ground on a surface grinder to a surface roughness of not less than Ra0.3, and finally, it is cut into the required size.

Citation Information

Patent Citations

  • Copper-molybdenum-and-copper-copper composite material for semiconductor high-power device and preparation method thereof

    CN109351976A

  • Preparation method of high-performance molybdenum copper alloy

    CN110885946A